"y''-3y'+2y=7e^{3x}, y_1=e^x."
We use a substitution: "y=y_1z=e^xz"
"y'=(e^xz)'=e^x(z+z')."
"y''=[e^x(z+z')]'=e^x(z+2z'+z'')."
Substituting the derivatives in the equation and reducing by "e^x" , we have
"z+2z'+z''-3(z+z')+2z=7e^{2x}\\to z''-z'=7e^{2x}"
We use a substitution: "z'=u."
"\\frac{du}{dx}-u=7e^{2x}". Let "t(x)=e^{-x}" . Multiply both sides by "t(x)".
"e^{-x}u'-\\frac{d(e^{-x})}{dx}u=7e^x \\to \\frac{d(e^{-x})u}{dx}=7e^{x}"
"\\int \\frac{d(e^{-x}u)}{dx}dx=\\int7e^{x}dx \\to e^{-x}u=7e^{x}+C_1\\to u(x)=e^x(7e^{x}+C_1)"
"z= \\int udx= \\int e^{x}(7e^{x}+C_1)=\\frac{7e^{2x}}{2}+C_1e^x+C_2"
"y=e^xz=e^x(\\frac{7e^{2x}}{2}+C_1e^x+C_2)"
Answer: "y_2=C_2e^{2x}", the general solution is "y=e^x(\\frac{7e^{2x}}{2}+C_1e^x+C_2)".
Comments
Leave a comment